2016
DOI: 10.1371/journal.pone.0146575
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of (+)-Usnic Acid against Non-Small Cell Lung Cancer Cell Motility

Abstract: Lichens are symbiotic organisms that produce various unique chemicals that can be used for pharmaceutical purposes. With the aim of screening new anti-cancer agents that inhibit cancer cell motility, we tested the inhibitory activity of seven lichen species collected from the Romanian Carpathian Mountains against migration and invasion of human lung cancer cells and further investigated the molecular mechanisms underlying their anti-metastatic activity. Among them, Alectoria samentosa, Flavocetraria nivalis, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 36 publications
(37 reference statements)
2
36
0
Order By: Relevance
“…UA prominently caused to apoptotic death in many cancer cells . We also found that UA induced apoptosis in LNCaP and MCF7 cells.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…UA prominently caused to apoptotic death in many cancer cells . We also found that UA induced apoptosis in LNCaP and MCF7 cells.…”
Section: Discussionsupporting
confidence: 64%
“…The most interesting is UA produced by Usnea species . UA has been reported in many studies that to be an antiproliferative agent, apoptosis inducer, and a cell cycle arrestor in different cancer cells, such as MCF7, HeLa, HCT‐116, A2780, HT‐29, HepG2, A549, Jurkat, HTB‐140, DU145, and PC‐3. We used MCF7 cells as the HDBC model, LNCaP cells as the HDPC model and the normal cells of the relevant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Invasion assays were performed in Boyden chambers (Corning, New York, NY, USA). Transwell chambers pre-coated with 1% gelatin were used, as previously described [ 29 ]. Cells (2 × 10 6 ) in 120 μL of medium (DMEM containing 0.2% bovine serum albumin dissolved in PBS) containing or lacking various concentrations of melatonin or 2-hydroxymelatonin were seeded in the upper chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary metabolites present in lichens include aliphatic, cycloaliphatic, aromatic, and terpenic compounds, which demonstrate significant biological and pharmacological effects including those of anti-inflammatory, antiviral, antibacterial, analgesic, antipyretic, anti-proliferative, and cytotoxic [17]. These compounds have demonstrated also antineoplastic activities in preclinical research in which revealed significant effects against cancer cells [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%